2013
DOI: 10.1098/rspb.2013.1140
|View full text |Cite
|
Sign up to set email alerts
|

The body beyond the body: expectation of a sensory event is enough to induce ownership over a fake hand

Abstract: ResearchCite this article: Ferri F, Chiarelli AM, Merla A, Gallese V, Costantini M. 2013 The body beyond the body: expectation of a sensory event is enough to induce ownership over a fake hand. Proc R Soc B 280: 20131140. http The body beyond the body: expectation of a sensory event is enough to induce ownership over a fake hand More than 100 papers have been published on the rubber hand illusion since its discovery 14 years ago. The illusion has been proposed as a demonstration that the body is distinguished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
141
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(165 citation statements)
references
References 45 publications
15
141
9
Order By: Relevance
“…Indeed, it is known that anticipation of a sensory stimulus and processing of the somatosensory stimulus itself engage similar brain [67], [68] and autonomic [17] activities. Then, Pearson correlations between heartbeat perception scores and normalized RSA response to NS, IS and FS in each task were performed to assess whether interoceptive sensitivity predicts autonomic reactivity in a social situation, compared to a non-social situation, as a function of different peripersonal space distances.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it is known that anticipation of a sensory stimulus and processing of the somatosensory stimulus itself engage similar brain [67], [68] and autonomic [17] activities. Then, Pearson correlations between heartbeat perception scores and normalized RSA response to NS, IS and FS in each task were performed to assess whether interoceptive sensitivity predicts autonomic reactivity in a social situation, compared to a non-social situation, as a function of different peripersonal space distances.…”
Section: Methodsmentioning
confidence: 99%
“…In general, how interoceptive sensitivity impacts on engagement in social situations is a relevant and not yet well researched issue. An interesting question arising from previous empirical investigations [15][17] is, for instance, whether and what extent interoceptive sensitivity affects the representation of one's peripersonal space, as a multisensory-motor interface between body and environment, in social circumstances. The definition of peripersonal space [18], [19] originates from electrophysiological studies based on visual–tactile neurons identified in the premotor area F4 and the ventral intraparietal area (VIP) of the monkey brain [20]–[22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result reflects an alteration of multisensory integration within the PPS due to changes in BSC. Finally, Ferri et al (2013) showed that the rubber hand illusion hand can be obtained even without touching the rubber hand by just presenting visual stimuli entering the rubber hand's PPS.…”
Section: Multisensory Integration Of Bodily Signals Is Constrained Bymentioning
confidence: 98%
“…In a previous study carried out on healthy volunteers [57], participants were seated with their right arm resting upon a table just below another smaller table. Thus, the real hand was hidden from the participant's view and a life-sized rubber model of a right hand was placed on the small table in front of the participant.…”
Section: Bodily Self and Schizophrenia: Loss Of Implicit Self-knowledmentioning
confidence: 99%